1996
DOI: 10.1099/0022-1317-77-8-1953
|View full text |Cite
|
Sign up to set email alerts
|

Frequent occurrence of recombinant potyvirus isolates

Abstract: We have performed a systematic search for recombination in the region encoding coat protein and the 3' non-translated region in natural isolates of potyviruses, the largest group of plant RNA viruses. The presence of recombination, and the localization ofthe cross-over points, were confirmed statistically, by three different methods. Recombination was detected or suspected in 18 out of 109 potyvirus isolates tested, belonging to four out of eight virus species, and was most prevalent in potato virus Y, clear i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
1
3

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(126 citation statements)
references
References 47 publications
3
119
1
3
Order By: Relevance
“…Detailed phylogenetic studies on potyviral strains gave evidence of numerous recombination events between strains, whereas when cucumoviruses were analysed, no evidence of recombination was observed (Revers et al, 1996 ;Candresse et al, 1997). Although this may in part be due to differences in the efficiency of detection in different virus systems, it is tempting to speculate on the existence of processes regulating RNA recombination that could be determined either by the virus itself (the RdRp and\or sequence-specific or structural signals in the viral RNA) or by the host.…”
Section: Recombination In Rna Virusesmentioning
confidence: 99%
“…Detailed phylogenetic studies on potyviral strains gave evidence of numerous recombination events between strains, whereas when cucumoviruses were analysed, no evidence of recombination was observed (Revers et al, 1996 ;Candresse et al, 1997). Although this may in part be due to differences in the efficiency of detection in different virus systems, it is tempting to speculate on the existence of processes regulating RNA recombination that could be determined either by the virus itself (the RdRp and\or sequence-specific or structural signals in the viral RNA) or by the host.…”
Section: Recombination In Rna Virusesmentioning
confidence: 99%
“…Proportionally, the amount of genetic variability produced after a single recombination event is larger than that produced by single point mutations. Although the importance of recombination was underappreciated in early studies of virus genome evolution, it is now recognized as a widespread phenomenon among positive-strand RNA viruses in animals (Grassly & Holmes, 1997;Holmes et al, 1999;Wilson et al, 1988) and plants (Nagy & Bujarski, 1993;Revers et al, 1996;Aranda et al, 1997;Olsthoorn et al, 2002;Bousalem et al, 2003;Cheng & Nagy, 2003;Moreno et al, 2004;Tan et al, 2004;Bonnet et al, 2005;Urbanowicz et al, 2005;Chare & Holmes, 2006;Weng et al, 2007), as well as in retroviruses such as human immunodeficiency virus type 1 Prljic et al, 2004;Althaus & Bonhoeffer, 2005;Galetto & Negroni, 2005), although it is a rare or even non-existent phenomenon among negativestrand viruses (Chare et al, 2003). There are several mechanisms by which RNA recombination may take place, the most common of which is homologous recombination (Lai, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Even if recombination is considered to be frequent within potyvirus populations (Bousalem et al, 2003;Moreno et al, 2004;Revers et al, 1996), our data indicate that recombination between different potyviruses is a rather uncommon event. A similar observation has been made by Meier and Truve (2006), who did not detect any recombinants in oat plants doubleinfected by two sobemoviruses (Cocksfoot mottle virus and Ryegrass mottle virus).…”
Section: Screening Double-infected Non-transgenic Plants and Single-imentioning
confidence: 68%
“…Recombination within potyviruses has been shown to occur by a template-switching model (Gal-On et al, 1998). Within potyviral populations recombination can be rather frequent (Revers et al, 1996) reaching up to 7% as shown for Watermelon mosaic virus (WMV; Moreno et al, 2004). Additionally, natural recombination crossover sites within the above mentioned viruses have been determined (Cervera et al, 1993;Glais et al, 2002;Glasa et al, 2004).…”
Section: Dietrich Et Almentioning
confidence: 99%